Analysis Of Mathematical Problem-Solving Ability In View Of Mathematical Disposition - Azizah, Dewi; Fadlikah, Vika (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
Problem solving is one-skills most importantly no could separated adri learning math. In the process of solving problems, students will not be separated from their positive attitude towards mathematics (mathematical disposition). On the other hand, the results of tests and observations during the pandemic show that the mathematical problem-solving ability of class X students of Gondang Vocational School is relatively low. Moment solve-problem math, students not enough motivated for solve it. Besides that, students feel less confident and unable to solve math problems. Goal writing article is to describe the mathematical problem-solving abilities of class X students of SMK Gondang in terms of mathematical dispositions. The research method used in article this is qualitative method. Class X TKR 4 has 26 students. Subjects are selected using purposive sample technique based on the results questionnaire categorization, taking into account learning activities students in learning mathematics. Data collection techniques include questionnaires, tests, and interviews. The data analysis techniques include data reduction, data presentation, and withdrawal conclusions referring to data processing Milles and Huberman. The research results show that position students dominant have a moderate level of disposition, and students who have the same level of disposition have different problem-solving abilities. This is because students have their own difficulties and mistakes in solving mathematics. Skills problem solving is based on the level of deep mathematical disposition post-pandemic learning, namely: students with a high disposition can fulfill four indicators of Polya problem solving, students with a moderate disposition are able to fulfill three indicators without re-examining the results and students with a low disposition can only fulfill one indicator that is understanding the problem